The Motivations and Barriers to Halal Supply Chain Implementation: A Case Study of the Pempek Industry in Palembang, Indonesia - Bayu Wahyudi; Tuwandi Juniarto; Anindita Rahmalia Putri; Yasmin; Mirza Bhilqis Jiratullah; Petrik Aulia Akbar (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to analyze the level of understanding, motivational factors, perceived impacts, and barrier factors related to halal certification adoption among pempek business actors in Palembang City using a statistical descriptive of 97 respondents. The analysis included validity and reliability testing using IBM SPSS Statistics v.26, followed by descriptive statistical analysis. The results indicate that respondents demonstrate a high level of understanding of halal certification, particularly regarding its conceptual meaning and business benefits. Motivation to obtain certification is primarily driven by the intention to enhance Muslim consumer trust and strengthen market credibility rather than by external incentives. The perceived impacts of halal certification are largely associated with increased consumer trust, improved product quality, and expansion of customer base, while financial gains are viewed as secondary outcomes. Although overall barriers are categorized as moderate, certification costs and administrative complexity remain the most significant constraints, especially for micro-scale enterprises. The findings suggest that halal certification functions as a credibility-based competitive strategy supported by strong normative awareness, yet constrained by structural and institutional challenges. Strengthening procedural simplification and institutional support mechanisms is essential to enhance sustainable halal certification adoption among micro and small food enterprises.